Ultrathin 2D Zirconium Metal–Organic Framework Nanosheets: Preparation and Application in Photocatalysis. Issue 16 (13th March 2018) - He, Ting; Ni, Bing; Zhang, Simin; Gong, Yue; Wang, Haiqing; Gu, Lin; Zhuang, Jing; Hu, Wenping; Wang, Xun
Abstract: Synthesizing ultrathin 2D metal–organic framework nanosheets in high yields has received increasing research interest but remains a great challenge. In this work, ultrathin zirconium‐porphyrinic metal–organic framework (MOF) nanosheets with thickness down to ≈1.5 nm are synthesized through a pseudoassembly–disassembly strategy. Owing to the their unique properties originating from their ultrathin thickness and highly exposed active sites, the as‐prepared ultrathin nanosheets exhibit far superior photocatalysis performance compared to the corresponding bulk MOF. This work highlights new opportunities in designing ultrathin MOF nanosheets and paves the way to expand the potential applications of MOFs. Abstract : Ultrathin zirconium‐porphyrinic metal–organic framework (MOF) nanosheets with thickness down to 1.5 nm are synthesized through a pseudo‐assembly–disassembly strategy. Owing to the their unique properties originating from their ultrathin thickness and highly accessible active sites, the as‐prepared ultrathin nanosheets exhibit far superior photocatalysis performance compared with the corresponding bulk MOF.